2,4-Dihydroxy-5-nitropropiophenone Oxime as a Gravimetric Reagent for Cu(II) - Kumar B. Patel, Nitin; Desai, K.K. (Asian Journal of Chemistry, 2016)
2,4-Dihydroxy-5-nitropropiophenone oxime (DHNPO) was developed as a new analytical reagent for gravimetric determination of Cu(II). In pH range of 3.0 to 6.0, this reagent gives a buff coloured precipitate with Cu(II). Interference of many cations and anions has been checked. Job's method and mole ratio method revealed that the stochlometry of the complex is 1 : 2, the Beer law is obeyed upto 7.62 ppm of Cu(II), The molar absorptivity at 520 nm was found to be 9.92 × 102 L mol-1 cm-1. The stability constant of the complex has been calculated from spectrophotometric data. The Cu(II) complex was found to have paramagnetic character. TGA studies were done on the Cu(II) complex. Energy of activation for decomposition step has been calculated using Broido method. The reagent has been successfully applied to the determination of Cu(II) in drain microtech solution.